Facile Fabrication of Polydopamine-Functionalized Titanium Dioxide Nano/Submicro-Particles on the NiTi Substrate for Highly Efficient Solid-Phase Microextraction of Benzotriazole Ultraviolet Filters from Environmental Water Samples - Huiju Wang; Shoujia Wang; Kang Li; Yulong Ma; Tianhong Zhou (Journal of Chemistry)
A new polydopamine-functionalized titanium dioxide nano/submicro-particles (PDA@TiO2NPs) coating was successfully constructed on the surface of NiTi substrate as a solid-phase microextraction (SPME) fiber. To obtain a stable and uniform PDA@TiO2NPs coating, the NiTi fiber was hydrothermally treated for in situ growth of titanium/nickel oxide composite nanosheets (TiNiOCNSs). Subsequently, the titanium dioxide nano/submicro-particles (TiO2NPs) were electrophoretically deposited on the TiNiOCNSs coating. Finally, the polydopamine (PDA) coating was modified on the TiO2NPs coating by self-polymerization of dopamine (DA). Scanning electron microscopy (SEM) of the new PDA@TiO2NPs@TiNiOCNSs@NiTi fiber showed a popcornlike nanostructure with a larger surface area and more adsorption sites. Benefitting from the abundant hydrogen bonding, rich π-electron system, and strong hydrophobicity, the functionalized PDA@TiO2NPs@TiNiOCNSs@NiTi fiber illustrated excellent extraction capability for benzotriazole ultraviolet filters (BUvFs) among typical aromatic compounds coupled to HPLC with UV detection. The main SPME conditions such as extraction and desorption time, extraction temperature, stirring rate, and ionic strength were examined and optimized one by one. Under the optimum conditions, the calibration curves presented good linearity for BUvFs in the ranges from 0.01 µg·L−1 to 300 µg·L−1, and the correlation coefficients (r) were above 0.9990. The limits of detection (LODs, S/N = 3) were between 0.005 µg·L−1 and 0.043 µg·L−1. RSD repeatability of intraday and interday for one fiber was less than 5.3% and 6.9%, respectively. Moreover enrichment factors (EFs) ranged from 63 to 218. The recommended method can completely extract and detect trace BUvFs in different environmental water samples. Furthermore, the new fiber shows good stability and high strength.